Diodo planar orgânico Schottky: construção e caracterização - Paquola, Alexandre Guidio [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Usually organic diodes are made with a semiconducting polymeric layer placed between two electrodes in a sandwich-like architecture. The fabrication process involves mainly two steps: a) film formation over a metallic substrate (bottom electrode) and b), metallic electrode deposition by thermal evaporation over the top surface. The main problem with this procedure is that the semiconductor film top surface becomes rough if compared with the bottom surface, which remains in contact with the substrate. Additionally the thermal evaporation of electrodes promotes diffusion of metal atoms into the semiconducting layer, making this interface not well defined. To avoid surface roughness and metal diffusion was developed, in this work, a bimetal (Au and Al) finger structure over which the semiconductor material was deposited. Undoped poly-o-methoxyaniline was deposited over the finger structure by drop casting and the doping was promoted by exposing the electrode-free surface to HCl acid (0.1 M). The devices current-voltage characteristic was monitored for different acid exposure time using a Keithley 2410 source/meter unity. Was verified that the diode characteristic curve shape is highly depend on the doping time, starting form a linear behavior up to a high quality diode curve. For acid exposure times higher than 250 s the diode characteristic curve starts to decay, pointing that acid diffusion was reached the finger electrode, causing electrode damaged. The lower diode ideality factor and turn-on voltage was  = 8 and VOP = 0.900  0.004 V, respectively. These values indicate that the minimum devices volume resistance was reached. Employing optimized exposure times was possible to design diodes with rectification ratio at about 25. Diode characterization in different temperatures indicates that the operation occurs typically by Schottky process

Normalmente díodos orgânicos são feitos com uma camada polimérica semicondutora colocada entre dois eletrodos numa arquitetura tipo sanduíche. O processo de fabricação envolve principalmente dois passos: a) formação do filme polimérico semicondutor sobre um substrato metálico (eletrodo inferior) e b) deposição de um eletrodo metálico por evaporação térmica sobre a superfície superior do filme polimérico semicondutor. O principal problema com este procedimento é que a superfície superior do filme semicondutor torna-se rugosa se comparada com a superfície inferior, que permanece em contato com o substrato. Além disso, a evaporação térmica promove a difusão dos átomos de metal para dentro da camada semicondutora, tornando esta interface não bem definida. Para evitar a rugosidade da superfície e a difusão de metal no filme semicondutor foi desenvolvido, neste trabalho, uma estrutura planar interdigitada bimetal (Au, Al) sobre a qual o material semicondutor foi depositado. Poli-o-metoxianilina não dopada foi depositada sobre a estrutura interdigitada por drop casting e a dopagem foi promovida através da exposição da superfície livre de eletrodos em ácido HCl (0,1 M). A característica corrente-tensão dos dispositivos foi monitorada em função de diferentes tempos de exposição a solução ácida usando uma fonte de corrente/tensão Keithley 2410. Foi verificado que a forma da curva característica do diodo é altamente dependente do tempo de dopagem, apresentando inicialmente um comportamento linear (Ôhmico) até ao de um díodo de alta qualidade. Para tempos de exposição de ácido superior a 250 s a curva característica do diodo passa a decair, apontando que a difusão do ácido alcança os eletrodos interdigitados, na face inferior do filme semicondutor, causando a degradação dos eletrodos. O menor valor obtido para o fator de idealidade do diodo e para a tensão de operação foi de...
Keywords: Semicondutores; Diodos semicondutores; Schottky, Diodos de barreira de; Eletrodos; Diodos